Screening of coconut (Cocos nucifera Linn.) shell for its bioactive secondary metabolites and analogous pharmacotherapeutic prospective - V Sreekala; Kamal Nayan Dwivedi; R Rajesh (Ancient Science of Life, 2024)
Background: Coconut shell is an inexpensive, easily available, and usually discarded material from the plant source Cocos nucifera Linn. belonging to the Arecaceae family. The internal administration of water boiled with endocarp of coconut fruit (coconut shell) is used as a folklore remedy in Kerala for treating metabolic disorders. This folklore claim has to be scientifically validated by comprehensive chemical profiling of coconut (Cocos nucifera Linn.) shell. Aim: The present study was designed to conduct a systematic screening of coconut shell for identification of its bioactive secondary metabolites and validation of its analogous pharmacotherapeutic potentials. Materials and Methods: The present research work is focused on the screening of dried ripe coconut (Cocos nucifera Linn.) shell for its bioactive secondary metabolites based on microscopic, histochemical, and phytochemical studies. Results: Characteristic presence of thin-walled fibers and fibrosclereids were observed in the powder microscopy of coconut shell. Histochemical studies were suggestive of the presence of lignified cells and tannins in the test drug. Further phytochemical studies of Cocos nucifera Linn. ascertained that the endocarp is abounded with diverse bioactive phytoconstituents like flavonoids, alkaloids, phenols, steroids, tannins, and saponins which possess varied antioxidant, anti-inflammatory, anti-obesity, and antidiabetic activities. Conclusion: The study outcome suggests coconut shell as a novel natural source of various bioactive secondary metabolites and these findings can be integrated for further researches exploring the comprehensive pharmacotherapeutic prospective of the test drug.